Feasibility and Safety Properties of Metabolic-Flow Anesthesia Driven by Automated Gas Control® in Pediatric Patients: A Prospective Observational Study - Emre Sertaç Bingül; Meltem Savran Karadeniz; Emre Şentürk; İrem Vuran Yaz; Ayşe Gülşah Atasever; Mukadder Orhan Sungur (Medicina)
Background and Objectives: Metabolic-flow (<0.35 L/min) anesthesia is practiced more often as manufacturers provide newer technologies, yet the benefits of metabolic-flow anesthesia have not been fully investigated. This study aimed to investigate the feasibility and safety of automated gas control (AGC®) mode, which provides metabolic-flow anesthesia, in a pediatric population. Materials and Methods: Pediatric surgery patients between 1 and 10 years of age were included in this prospective observational trial. After intravenous induction and safe orotracheal intubation, AGC® was initiated, and total sevoflurane consumption (mL) and wash-in speed-based sevoflurane consumption data were collected to measure feasibility. For safety, inspired (FiO2), alveolar (FAO2), and expired (FEO2) oxygen concentration data, and inspired and alveolar sevoflurane (FiSevo and FASevo, respectively) concentration data, were recorded. Changes in fresh gas flow (FGF) throughout the procedure and postoperative recovery data were also compared. Results: A total of 130 patients were eligible for this study, and 121 patients were included in the analyses; 30 patients had a wash-in speed of 4 (WI4) and 91 patients had a wash-in speed of 8 (WI8) at follow-up. The total mean sevoflurane consumption was 9.35 ± 4.93 mL for a median surgery duration of 100 min. WI8 patients consumed more sevoflurane (9.92 ± 5.08 mL vs. 7.79 ± 4.19 mL, p = 0.04). At the 15th and 30th minutes, the FGF dropped under minimal flow and metabolic flow limits, respectively (p < 0.001). The times to extubation and obeying commands were shorter in WI8 patients (8 (5–10) vs. 11 (5–15) p = 0.03, and 9.5 (5–10.5) vs. 13 (9–17) p < 0.01). Conclusions: Maintenance with AGC® may offer up to 40 h of anesthesia, considering that the volume of a sevoflurane bottle is 250 mL, reflecting exceptional savings compared to conventional anesthesia management. Metabolic flow anesthesia driven by AGC® is feasible and safe in pediatric anesthesia practice.